What is the best way to measure blood pressure? - Fernando Nobre; Décio Mion Júnior (Annals of Circulation - Peertechz Publications, 2021)
Since Scipiano Riva-Rocci [1] created the device to measure Blood Pressure (BP), more than a century has passed with gains in knowledge of this way of assessing BP. Currently, the methods for assessing blood pressure in the 24 hours using devices capable of making these records are well established [2].